A study of the application of computer-assisted language learning (CALL) approach in the teaching of reading comprehension skills to primary four students of S.K. Garland, Kuching / Sedai Gara - Gara, Sedai (Universiti Teknologi MARA, Sarawak, 2005)
This study investigated the effects of computer-assisted language learning on reading comprehension Text on Primary Four students of SK. Garland, Jalan Batu Kawa, Kuching. Thirty students were selected and assigned to do the Control and Experimental Tests. They were taught using the CALL method. They watched the picture/story together with the audio definition, texts and exercises. The time allocated for the lessons was roughly one week, which was equivalent to one hundred and fifty minutes (5 periods of 30 minutes) before each test. The test was given on the sixth English period of the week. There were six (6) Experimental Tests altogether which was administered in alternate week.